Classification of War - YESEVİ, ÇAĞLA GÜL (Oxford: Inter-disciplinary Press, 2011)
War will be defined in broader perspective. War between nation-states will be disregarded. War comprises organized psychological pressures, all kinds of restraints, physical and psychological abuses, usage of aggressive terminology, strict and dogmatic political and social thoughts. In that sense, first category of war is war against women especially in my own society, people living in Turkey including both Turks and Kurds. Women have been facing religious pressures as veiling. Some other women have demanded the freedom of veiling in the official life. They haven’t been educated as men. They have been beaten, forced to do all households. They have been forced to get married in their early ages. The arranged marriages and polygamy have been other problems of women. It was settled in the minds, myths, terminology, narratives, and customs, social, economic and political life of people. Secondly, terrorism will be investigated. The history and activities of terrorist organization, Kurdistan Workers’ Party against Turkey will be revealed. Thirdly, the state’s war against its own citizens will be explained. This war could also be defined with the war between the government and the people. Both democratic and authoritarian states through party in the power could wage war against their own citizens by creating Fear Empire. Governments could use their legislative powers against citizens who have antagonistic ideas. Economic support has been given to supporters of government. The causes of judicial case related to Ergenokon Crime organization will be stated. Allegedly, this organization comprising nationalist and secular intellectuals and members of high military command tried to form coup d’état against government of Justice and Development Party. Many people were detained, long trial process has been continuing.
Keywords: Savaş; Sosyal Yönler; Siyasi ve Sosyal Görüşler; War; Social Aspects; Political and Social Views